0393 Open-Loop Audio-Visual Stimulation for Insomnia in Older Adults with Osteoarthritis Pain. (27th April 2018) - Tang, J; McCurry, S M; Riegel, B; Pike, K C; Vitiello, M V
Abstract: Introduction: Human brainwaves mimic frequencies of stimuli received. People with chronic insomnia often have excessive beta/gamma waves (12–100 Hz), indicative of cortical hyperarousal. We tested an open-loop Audio and Visual Stimulation (AVS) program that progressively downward stimulates brainwaves to induce delta (1–3 Hz) brainwaves and improve sleep. Methods: We conducted a small randomized controlled trial in 30 older adults (mean age 68.0 ± 5.1) with clinically significant co-morbid insomnia and osteoarthritis (OA) pain. The Procyon (MindPlace) AVS device was used to stimulate brainwaves to change from 8Hz to 2Hz over 30 minutes in the experimental group (E). The control group (C) received placebo AVS that idled below 0.5Hz, outside of the brainwave entrainment range. Participants used AVS devices to self-administer stimuli at bedtime nightly for two weeks. We measured sleep (Insomnia Severity Index-ISI, Pittsburgh Sleep Quality Index-PSQI), pain (Brief Pain Inventory), and depression (Patient Health Questionnaire-9) at baseline and post-treatment. Post-hoc analyses focused on examining AVS impact for the 11 participants (mean age 69.8 ± 4.2) with sleep latency complaints (≥30 minutes). Results: Self-reported within-group improvement of ISI (E: p =.019; C: p =.005), PSQI (E: p =.005; C: p =.004), was observed in both E and C groups. Improvements in pain ( p =.035) and depression ( p =.003) were observed only in the experimental group. Between-group comparisons were non-significant, and the AVS effect sizes (Cohen's d) for sleep improvements were small: ISI = 0.18; PSQI = 0.03. In the sleep onset difficulty sub-group analyses, the pre-post sleep effect sizes for the experimental versus control groups were increased considerably, relative to the total sample (d = 0.41 and 0.60 for ISI and PSQI, respectively). Conclusion: Open-Loop AVS has the potential to induce delta activity and may be effective for sleep promotion, particularly in insomniacs with sleep onset complaints. Support (If Any): Project supported by Research & Intramural Funding Program, School of Nursing, University of Washington.